Analisis Elastisitas Pendapatan Rumah Tangga di Indonesia - Hafizah, Dian; Hakim, Dedi Budiman; Harianto, Harianto; Nurmalina, Rita (Jurnal Ilmu Pertanian Indonesia, 2021)
Demand for food products is inevitable, this condition is related to food products as a staple food for the sustainability of human life. In Indonesia, the demand for food depends very much on the needs of the people. The purpose of this study is to analyze food demand in Indonesia which is divided into 4 categories of regions: rich cities, poor cities, rich villages, and poor villages need through research that can be obtained about getting assistance in accordance with the consumption demand of people in Indonesia. The research method used secondary data with panel data types obtained from SUSENAS data. The analytical method used to estimate the demand system was through econometrics demand, namely the QUAIDS model and then the data were processed using the SAS program. The results showed a comparison of the total number of households allocated specifically for food if sorted out, namely poor villages were higher then followed by poor cities, rich cities, and rich villages. When there is a change in income, poor rural households and poor cities when the public still responds by allocating a large part of their budgets to very basic trade such as other food and tobacco, rice, other oils, and household fats in rich villages and rich cities provide more responses to allocating their incomes to the trade in meat, fruits, vegetables, fish, eggs, milk, and processed foods. Keywords: Quadaric Almost Ideal System, income elasticity, consumption, demand food